Ultra-broad NIR emission from two-site Cr3+ occupation in fluoride phosphor via composition-driven structural transformation. (December 2022) - Nie, W.D.; Zuo, J.X.; Yang, S.; Li, Y.; Zou, W.F.; Chen, G.; Wu, S.H.; Wu, D.; Liu, S.B.; Peng, J.Q.; Han, L.; Ye, X.Y.
Abstract: Cr 3+ -activated fluoride-based near-infrared (NIR) phosphors have attracted wide attention from researchers due to their high luminous efficiency and high thermal stability. However, the practical application of this type of phosphors is severely hindered by their narrow emission. In this work, a structural transformation from Li3 GaF6 to LiMgGaF6 was successfully obtained by stoichiometric control during hydrothermal process, leading to an NIR phosphor LiMgGaF6 :Cr 3+ with broadband emission ranging from 650 to 1150 nm. With the replacement of Li by Mg atom of Li3-2 x Mg x GaF6 :Cr 3+ (0 ≤ x ≤ 1), the full width at half maximum of emission band can be broaden to 189.9 nm from 140 nm. This ultra-wide NIR emission of fluoride phosphor is caused by double-site Cr 3+ occupation, which is verified by activator concentration-dependent spectra, Rietveld structural refinement, and density functional theory first-principles calculations. Despite the wide-band NIR emission, the LiMgGaF6 :Cr 3+ phosphor shows relatively high quantum efficiency of 42.3% and high thermal stability, which maintains 50% of its initial intensity at 400 K. The ultra-broadband NIR emission of LiMgGaF6 :Cr 3+ has potential applications as a light source in ingredient identification, and the strategy of multisite occupation of Cr 3+ through compositional regulation opens a new way for the exploration of Cr 3+ -doped broadband NIR fluoride phosphors. Highlights: A novel LiMgGaF6 :Cr 3+ with an ultra-wide NIR emission was synthesized. The LiMgGaF6 :Cr 3+ phosphor exhibits a wide FWHM of ∼189 nm. Double-site induced emission is first reported in Cr 3+ -activated fluoride phosphors.